Jaffe-Campanacci syndrome or neurofibromatosis type 1: a case report of phenotypic overlap with detection of NF1 gene mutation in non-ossifying fibroma - Silvia Vannelli; Raffaele Buganza; Federica Runfola; Ilaria Mussinatto; Antonio Andreacchio; Luisa de Sanctis (BMC, 2020)
Abstract Background Jaffe-Campanacci syndrome is characterized by multiple non-ossifying fibromas, café-au-lait macules and giant cell granulomas of the jaw. Even if the association between all these peculiar features and neurofibromatosis type 1 have been described, it has not yet been clarified whether Jaffe-Campanacci syndrome represents a distinct entity or it can be regarded as a neurofibromatosis type 1 subtype. Case presentation The patient here described is a young boy, who fulfilled the clinical diagnostic criteria for both syndromes. He had a complex clinical history with café-au-lait macules, axillary and inguinal freckling, multiple non-ossifying fibromas, giant-cell granuloma of the jaw, neurofibromas, plexiform fibroma, ocular Lisch nodules, optic chiasmatic- hypothalamic glioma, pseudarthrosis, scoliosis, short stature, vascular anomalies, seizures. Molecular analysis of the NF1 gene both on blood cells and non-ossifying fibroma's biopsy tissue allowed the detection of a novel variant within the coding region, NM_000267.3:c.2789_2791delATC(p.Tyr930_Pro931delinsSer), with loss of heterozygosity (second hit mutation) in the non-ossifying fibroma. Conclusion This result indicates that every patient with clinical features of Jaffe-Campanacci syndrome should be further evaluated to detect features related to neurofibromatosis type 1 and genetically investigated for mutations in the NF1 gene, since this could lead to a definite diagnosis, but also could clarify and quantify the real genotype-phenotype overlap between neurofibromatosis type 1 and Jaffe-Campanacci syndrome.